Fundamentals of quantum entanglement - Duarte, F. J. (Frank J.) (IOP (Series). Release 22., 2022)
Quantum entanglement (QE) has rapidly become a subject of great interest in academia, industry, and government research institutions. This book builds on the first edition of Fundamentals of Quantum Entanglement to provide a transparent and more insightful introduction for graduate students, scientists, and engineers. It is also a highly useful education tool for those practitioners that were not aware of the physical origin of quantum entanglement: the Dirac-Wheeler-Pryce-Ward physics. The new edition includes an expansion on topics such as quantum entropy and quantum time. The book provides a direct, practical, and transparent introduction to the principles and physics of quantum entanglement. It does so whilst utilizing an interferometric approach based on Dirac-Feynman superposition probability amplitudes. Part of IOP Series in Coherent Sources, Quantum Fundamentals, and Applications.